Mastering the Risky Business of Public-Private Partnerships in Infrastructure. (Washington, D.C. : International Monetary Fund, 2021)
Investment in infrastructure can be a driving force of the economic recovery in the aftermath of the COVID-19 pandemic in the context of shrinking fiscal space. Public-private partnerships (PPP) bring a promise of efficiency when carefully designed and managed, to avoid creating unnecessary fiscal risks. But fiscal illusions prevent an understanding the sources of fiscal risks, which arise in all infrastructure projects, and that in PPPs present specific characteristics that need to be addressed. PPP contracts are also affected by implicit fiscal risks when they are poorly designed, particularly when a government signs a PPP contract for a project with no financial sustainability. This paper reviews the advantages and inconveniences of PPPs, discusses the fiscal illusions affecting them, identifies a diversity of fiscal risks, and presents the essentials of PPP fiscal risk management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fiscal Risks; National Government Expenditures and Related Policies; Other Public Investment and Capital Stock; Public Administration; Public Sector Accounting and Audits